The significance of religious key terms and their new meanings in Al-Faruqi’s Al-Tawhid: its implications for thought and life / Fadzilah Din - Din, Fadzilah (2015)
One of the most brilliant contributions of Ismail Raji al-Faruqi (1921-1986) is in the realm of Islamic Thought. His masterpiece Al-Tawhid: It’s Implications for Thought and Life is indeed a great and refreshing contribution in the realm of modern Islamic Worldview. In view of the title above, this paper will discuss the religious terminologies that have been given new meanings and thus have new implications in Al-Faruqi’s Al-Tawhid. While there are many religious terms that can be studied in Al-Tawhid, the terms which will be analysed in this paper are ilah, tawhid, iman, ibadah and ummah. The old meanings of these terms will be compared and contrasted with the new ones and the implications to Islamic practice will be discerned from them. The result of the analysis is one that can be said to be a contextualization of Islamic terminologies to modern time.